Сучасні методи, інформаційне, програмне та технічне забезпечення систем керування організаційно-технічними та технологічними комплексами - Національний університет харчових технологій (My University, 2018)
У матеріалах конференції наведено доповіді за напрямами: автоматизація процесів управління технологічними процесами та комплексами, ієрархічні системи управління та інформаційні системи управління у виробництві та освіті. Видання містить програму і матеріали Міжнародної науково-технічної конференції. The materials of the conference are presented in the following areas: automation of processes of management of technological processes and complexes, hierarchical control systems and information management systems in production and education. The publication contains the program and materials of the International Scientific and Technical Conference. The materials of the conference will be useful for scientific and engineering workers, industrialists, potential investors, students of higher educational institutions and all those involved with the food industry and automation.
Keywords: системи керування; автоматизація процесів керування; технологічні процеси; технологічні комплекси; ієрархічні системи управління; control systems; automation of management processes; technological processes; technological complexes; hierarchical control systems